IABSE Symposium, Venice 2010: Large Structures and Infrastructures for Environmentally Constrained and Urbanised Areas 2010
DOI: 10.2749/222137810796025537
|View full text |Cite
|
Sign up to set email alerts
|

Structural Assessment of ASR/DEF-Affected Bridge Bent Caps

Abstract: <p>As part of a large-scale experimental study of ASR/DEF-affected bridge bent caps, the accuracy and conservatism of two structural assessment techniques were examined. The crack width summation and elastic rebound techniques were selected for their potential to provide fast, sufficiently accurate estimates of the expansion due to ASR/DEF. These expansion estimates are ultimately valued for their ability to provide clear insights into the behaviour of affected structures. Comparison of the estimates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Distress originates from the formation of a chemically produced gel within hardened concrete and the subsequent swelling of the gel in the presence of a sufficient quantity of moisture supplied internally (i.e., within the pore structure for hydration) or externally (e.g., from the atmosphere or surrounding water). ASR expansion behavior in concrete elements is well known to be influenced by the presence of embedded, deformed reinforcement, which serves as a passive restraint to expansions . Understanding how different reinforcing details, such as reinforcement ratios, orientations, and layouts, influence the development and multiaxial distribution of ASR‐induced expansions is key in establishing the in‐service performance and functionality of ASR‐affected structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distress originates from the formation of a chemically produced gel within hardened concrete and the subsequent swelling of the gel in the presence of a sufficient quantity of moisture supplied internally (i.e., within the pore structure for hydration) or externally (e.g., from the atmosphere or surrounding water). ASR expansion behavior in concrete elements is well known to be influenced by the presence of embedded, deformed reinforcement, which serves as a passive restraint to expansions . Understanding how different reinforcing details, such as reinforcement ratios, orientations, and layouts, influence the development and multiaxial distribution of ASR‐induced expansions is key in establishing the in‐service performance and functionality of ASR‐affected structures.…”
Section: Introductionmentioning
confidence: 99%
“…Results from these studies have shown that expansions in restrained directions are less than those in the unreinforced directions comprising the same RC element. Other studies have examined the behavior of triaxially reinforced cubes, blocks, or beams with cross‐sectional dimensions ranging from 250 mm to beyond 1,000 mm. Various reinforcement ratio combinations have been incorporated in these specimens by way of individual straight bars for cubes and blocks or longitudinal bars and stirrups for beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither the number of reinforced directions, in this case two, nor the development of the mid‐depth cracks is believed to be causation for this behavior. Existing expansion data collected on beams with triaxial restraint (longitudinal bars and closed stirrups) and no significant isolated cracks have evidenced that expansions can stop in one direction and continue in others . In those cases, the heavily reinforced longitudinal direction stopped expanding.…”
Section: Resultsmentioning
confidence: 99%
“…Despite different specimen sizes, materials, and loading conditions during ASR generation, the biaxially restrained specimen discussed in this paper and the aforementioned triaxially restrained beams were similarly reinforced in one direction with No. 11 bars lumped in top and bottom layers.…”
Section: Resultsmentioning
confidence: 99%